Surgical Removal of an Extrauterine Device Migrating to Appendix - Uysal, Gulsum (Case Rep Med, 2016)
Intrauterine devices (IUDs) remain highly effective reversible family planning methods in developing countries. We aimed to report one of the complications of extrauterine and intrauterine devices. A 44-year-old woman was admitted to our hospital with mislocated intrauterine device and abnormal uterine bleeding. Extrauterine IUD device was proven by ultrasound and X-ray. She had normal blood test count with a negative pregnancy test. There are several cases of complications with intrauterine devices, but this is the first case report about an extrauterine IUD embedded by inflame enlarged appendix presenting with abnormal uterine bleeding. Although intrauterine devices are a common safe method for contraception, there is no risk-free insertion even with advanced ultrasounds. A regular self-examination should be taught to the patients and ultrasonography should be performed in the follow-up of the patients especially for inserted devices during lactation period. Extrauterine IUDs can be successfully removed by laparotomy.